1988
DOI: 10.2331/suisan.54.1415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified ice storage on the quality and prevention of darkening discoloration of shrimp Solenccera prominentis.

Abstract: To develop a convenient method for preserving shrimp on boat and during processing, several ice storage procedures were investigated. Based on the assessments of microbial growth, volatile base nitrogen (VB-N), extractable nitrogen (AA-N), inosine 5'-monophosphate (IMP) ratio and sensory evaluation, the decomposition of shrimp meat was retarded by storing in an ice-salt mixture (crushed ice and 3% NaCl, w/w), in the ice-salt mixture and 0.1% potassium sorbate, or in the ice-salt mixture, 0.1% potassium sorbate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…After 4 d, some of the shrimp held on ice presented black spots in the head (cephalothorax); the shrimp packed in both mixtures did not. These results are in agreement with Jiang and Lee (1988) and Yamagata and Low (1995), who reported darkening in the shrimp head after 4 to 5 d on ice. At the end of storage (7th and 9th d), melanosis developed in the iced shrimp (score 4), which exhibited black spots both on the head and tail.…”
Section: Sensory Evaluationsupporting
confidence: 93%
See 2 more Smart Citations
“…After 4 d, some of the shrimp held on ice presented black spots in the head (cephalothorax); the shrimp packed in both mixtures did not. These results are in agreement with Jiang and Lee (1988) and Yamagata and Low (1995), who reported darkening in the shrimp head after 4 to 5 d on ice. At the end of storage (7th and 9th d), melanosis developed in the iced shrimp (score 4), which exhibited black spots both on the head and tail.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…Decreases in IMP values were observed for all batches, and contents of approximately 1.7, 1.8, 2.6, and 2.8 mol/g were attained at the end of storage, respectively, for air-stored (batches CE and C) and atmosphere packed (batches F and G) shrimp, indicating a higher degradation rate for the former lots (72%) than for shrimp held in the mixtures (57%). IMP degradation between 36% and 100%, for 5 to 12 d of ice storage, have been reported for several shrimp species (Stone 1971;Flick and Lovell 1972;Fatima and others 1981;Jiang and Lee 1988). The same authors observed the highest degradation during the first 4 to 6 d.…”
Section: Nucleotides and Degradation Productsmentioning
confidence: 60%
See 1 more Smart Citation
“…IMP and hypoxanthine have been reported to be good indices for assessing shrimp quality (Fatima et al, 1981). Ho et al (1986) and Jiang and Lee (1988) demonstrated a significant correlation between the IMP ratio and shrimp quality. In the current study, the IMP ratio in both prawn treatments was high I even after the 26 hr storage period (Table 2).…”
Section: Changes In Atp and Its Relative Compounds And Imp Ratio Of Pmentioning
confidence: 99%
“…Many studies have evaluated the application of partial freezing (Uchiyama and Kato 1974), addition of chemicals (Niwa 1978;Bailey and Fieger 1954;Farber 1954;Fieger et al 1956), mixture of crushed ice and NaCl (Ho et al 1986;Jiang and Lee 1988), and modified atmosphere (Lannelongue et al 1982;Layrisse and Matches 1984;Reppond and Collins 1983), to fish and shellfish to extend the storage life. However, little is known about the mechanism by which these methods influence storage qualities.…”
Section: Introductionmentioning
confidence: 99%